2021
DOI: 10.3389/fbioe.2021.708137
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Disc Herniation Automatic Detection in Magnetic Resonance Imaging Based on Deep Learning

Abstract: Background: Lumbar disc herniation (LDH) is among the most common causes of lower back pain and sciatica. The causes of LDH have not been fully elucidated but most likely involve a complex combination of mechanical and biological processes. Magnetic resonance imaging (MRI) is a tool most frequently used for LDH because it can show abnormal soft tissue areas around the spine. Deep learning models may be trained to recognize images with high speed and accuracy to diagnose LDH. Although the deep learning model re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 29 publications
1
39
2
Order By: Relevance
“…In addition, using more data validation sets over 3500 images may increase YOLO performance [ 93 ]. However, the current study using a small-scale validation set under 350 images showed good performance [ 42 ]. Therefore, this study used a small-scale validation set using plantar pressure images and achieved a suitable YOLO performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, using more data validation sets over 3500 images may increase YOLO performance [ 93 ]. However, the current study using a small-scale validation set under 350 images showed good performance [ 42 ]. Therefore, this study used a small-scale validation set using plantar pressure images and achieved a suitable YOLO performance.…”
Section: Discussionmentioning
confidence: 99%
“…Using deep learning for object detection is widely used in biomedical applications [ 40 , 41 , 42 ]. For example, the deep learning model can identify plantar pressure patterns for early abnormal detection of foot problems [ 43 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on profiles of paravertebral muscles, the Image J 1.53 software program (United States National Institutes of Health, Bethesda, Maryland) was used to calculate their cross-sectional areas. The researcher who performed this assay was blinded to the pain site and to other related information of participants ( Tsai et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…However, since the image will be similar to the original image, the risk of overfitting, i.e., a decrease in the performance on the test dataset due to the prediction model fitting to match into the training dataset, cannot be ruled [57][58][59][60][61][62][63][64][65][66][67][68]. Thus, data augmentation effectively enables learning with a small number of data.…”
Section: Angles and Data Split In Deepsnap-dl With Digits And Python ...mentioning
confidence: 99%